BIMBINGAN TEKNIS DALAM MENGHADAPI OLIMPIADE SAIN NASIONAL BIDANG INFORMATIKA PADA SMA NEGERI 2 KOTA JAMBI (MATERI PEMOGRAMAN WEB) - Rasywir, Errisya; Irawan; Pahlevi, Riza; Salwa, Shakira (Jurnal Pengabdian Masyarakat UNAMA, 2024)
In dealing with OSN in the field of informatics, not all schools provide technical guidance. This is important to do considering that in ICT material, the output of material taught at school does not yet produce a simple application, while one of the assessments is that OSN participants are required to present the application. The importance of carrying out this technical guidance lies in the need to prepare participants optimally in facing OSN in the Informatics Field. Laravel was chosen as the focus of learning because it is a popular PHP framework and provides an organized structure and advanced features for developing web applications. With technical guidance, it is hoped that participants will be able to master web programming skills using Laravel, so that they can produce simple applications that can be applied in schools or the community. Thus, they are not only ready to take OSN Informatics well, but also have practical skills that can be useful in everyday life.